2022
DOI: 10.1155/2022/9256401
|View full text |Cite|
|
Sign up to set email alerts
|

On-Load Electromagnetic Compatibility Test and Simulation Closed-Loop of the Electric Drive System of New Energy Vehicles

Abstract: In order to solve the problem of high-amplitude and high-frequency interference generated by the electric drive system of new energy vehicles, the author proposes a closed-loop research method for on-load electromagnetic compatibility testing and simulation for electric drive systems of new energy vehicles. The method includes EMC design of the electric drive system on-load test equipment, establishment of a conducted EMI simulation platform for the electric drive system under load conditions, and optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With the increasing number of high-power power electronic equipment and the rapid improvement of equipment performance, the resulting electromagnetic interference becomes more and more serious, which also makes the electromagnetic interference and electromagnetic compatibility problems of power systems receive more and more attention and attention [26]. The problem of electromagnetic interference was first proposed in 1881 by the British scientist Heaviside, usually high-power power electronic equipment radiation electromagnetic interference generated by its own special structure or radiation body, may cause electronic or communication devices, equipment, or system performance degradation or even failure, but also may cause damage to other living or non-living tissue [27] when high-power power electronic equipment working in the low-frequency band The electromagnetic interference is mainly conducted electromagnetic interference [28]. Researchers in Japan have studied and analyzed the electromagnetic interference in DC-DC power converters, and found that the very high voltage variation dv/dt in the switching devices is prone to common mode interference, the parasitic capacitance formed between the switching device and the ground plane provides a conduction path for common mode interference, and the structure of some switching devices also determines the size of the parasitic capacitance [29].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing number of high-power power electronic equipment and the rapid improvement of equipment performance, the resulting electromagnetic interference becomes more and more serious, which also makes the electromagnetic interference and electromagnetic compatibility problems of power systems receive more and more attention and attention [26]. The problem of electromagnetic interference was first proposed in 1881 by the British scientist Heaviside, usually high-power power electronic equipment radiation electromagnetic interference generated by its own special structure or radiation body, may cause electronic or communication devices, equipment, or system performance degradation or even failure, but also may cause damage to other living or non-living tissue [27] when high-power power electronic equipment working in the low-frequency band The electromagnetic interference is mainly conducted electromagnetic interference [28]. Researchers in Japan have studied and analyzed the electromagnetic interference in DC-DC power converters, and found that the very high voltage variation dv/dt in the switching devices is prone to common mode interference, the parasitic capacitance formed between the switching device and the ground plane provides a conduction path for common mode interference, and the structure of some switching devices also determines the size of the parasitic capacitance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%